Estimating changes in emergency department visits associated with floods caused by Tropical Storm Imelda using satellite observations and syndromic surveillance. (March 2022) - Ramesh, Balaji; Jagger, Meredith A.; Zaitchik, Benjamin F.; Kolivras, Korine N.; Swarup, Samarth; Yang, Biru; Corpuz, Bianca G.; Gohlke, Julia M.
Abstract: Background: Satellite observations following flooding coupled with electronic health data collected through syndromic surveillance systems (SyS) may be useful in efficiently characterizing and responding to health risks associated with flooding. Results: There was a 10% (95% Confidence Interval (CI): 1%–19%) increase in asthma related ED visits and 22% (95% CI: 5%–41%) increase in insect bite related ED visits in the flooded ZCTAs compared to non-flooded ZCTAs during the flood period. One month following the floods, diarrhea related ED visits were increased by 15% (95% CI: 4%–27%) for flooded ZCTAs and children and adolescents from flooded ZCTAs had elevated risk for dehydration related ED visits. During the protracted period (2–3 months after the flood period), the risk for asthma, insect bite, and diarrhea related ED visits were elevated among the flooded ZCTAs. Effect modification by reported age, ethnicity and race was observed. Conclusion: Combining satellite observations with SyS data can be helpful in characterizing the location and timing of environmentally mediated adverse health outcomes, which may be useful for refining disaster resilience measures to mitigate health outcomes following flooding. Highlights: Tropical Storm Imelda flooding was associated with increased pregnancy-related, diarrhea, asthma, and insect bite ED visits. The flooding was also associated with increased ED visits related to dehydration among children and adolescents. Merging satellite observations with syndromic surveillance data aids in characterization of flood-related health outcomes.